System Identification and Control of Direct Current Motor - Zaiton, Muhammad Akmal; Ngadengon @ Ngadungon, Rafidah (Evolution in Electrical and Electronic Engineering, 2022)
The use of Direct Current (DC) motors today is very widely used whether in industry, hobby and education. At the industrial level, machines often use it to control things. The energy used by this DC motor is from electrical to mechanical energy. Process control is always used in industry, and motor speed is very important to control something. Proportional (P), Proportional Integral (PI), Proportional Derivative (PD) and Proportional Integral Derivative (PID) controllers are used to control the speed of the DC motor. The input data voltage and output data speed were taken to be used in the system identification to the mathematical model that will be used in the controller. In this project, MATLAB is used entirely to obtain data, and mathematical models, used in simulations and run-on DC motors. Based on the experiment, a comparison between P, PI, PD, and PID shows that the PID controller gives better performance.